Tourist Preferences and Satisfaction in Karangasem Virgin Beach, Bali - Arsana, I Gede Eka; Budi, Agung Permana; Sulasmini, Ni Made Ayu (Journal of Business on Hospitality and Tourism, 2018)
The development of Virgin Beach which has not been maximized has caused many complaints from tourists, both aspects of completeness of facilities, accessibility. Tourist preferences and satisfaction are important factors in developing Virgin Beach to make it better in the future. This study aims to find out the preferences and satisfaction of tourists in Virgin Beach, Karangasem, Bali. This type of research is descriptive quantitative, the number of samples of 40 visiting tourists taken using incidental sampling techniques. Questionnaires that are distributed using a Likert scale have been tested for validity and reliability. Data were analyzed through descriptive statistics with the assessment categorization method based on the average score and IPA (importance performance analysis) with a method of looking for gaps between expectations and performance. The results of this study conclude that tourist preferences in Virgin Beach are good, have an average value of 3.6 in the interval of 3,5 - 4,2. While tourist satisfaction shows from 5 variables, namely: reliability, responsiveness, assurance, empathy and tangible evidence, only responsiveness and assurance variables that have performance in accordance with tourist expectations and are able to satisfy tourists while physical evidence and reliability variables have lower performance from the expectations of tourists so that they have not been able to support the satisfaction of tourists on Virgin Beach and the empathy variable is not too expected by tourists to support their satisfaction at Virgin Beach. And it is necessary to develop from the aspect of tourist facilities, and improve service performance.